Assessment of knowledge about post exposure prophylaxis of HIV among medical, nursing and paramedical students in hospital and laboratory practice - A., Dulcie Celia; S., Mohamed Thajudeen; B., Meenakshi; J., Ezhil Ramya (International Journal of Basic & Clinical Pharmacology, 2017)
Background: India has 2.1 million of people living with HIV, and places in third-largest population of people infected with the HIV after South Africa and Nigeria. It is thus important for health care providers including medical, nursing and paramedical students to have adequate knowledge on PEP for HIV to protect themselves prior to starting their life long career. Methods: Cross-sectional study was conducted among 200 medical, nursing and paramedical students in Tirunelveli medical college from December 2016 to February 2017. A pre-designed questionnaire was used to collect data. Results were summarized in percentages and presented in tables. Results: A total of 96 (48%) males and 104 (52%) females responded in the study. Though many (87%) had heard about PEP, just 31 (15.5%) had received formal training on PEP for HIV. Only 81 (40.5%) knew the ideal PEP regimen and 88 (44%) knew the correct drug regimen. The majority 196 (98%) considered PEP was important and significant 178 (89%) considered themselves to be at risk of acquiring HIV at work, with 46 (23%) having experienced an exposure in the past. Of those exposed, only 21 (45.7%) received PEP. Conclusions: This study shows that knowledge, attitude and practice towards PEP for HIV is inadequate. A formal PEP training centre with proper guidelines is recommended for medical, nursing and paramedical students.